Programmed death‐ligand 1 expression in gastric cancer: correlation with mismatch repair deficiency and HER2‐negative status. (19th April 2018) - Wang, Lei; Zhang, Qiongyan; Ni, Shujuan; Tan, Cong; Cai, Xu; Huang, Dan; Sheng, Weiqi
Abstract: Gastric cancer (GC) is one of the most common malignancies. Immunotherapy is a promising targeted treatment. The immune regulatory programmed death‐1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) axis has been used as a checkpoint target for immunotherapy. Currently, considerable discrepancies exist concerning the expression status of PD‐L1 and its prognostic value in GC. We aimed to evaluate the expression rates of PD‐L1 in GC, and further assess its relationship with mismatch repair (MMR), and human epidermal growth factor receptor 2 (HER2) status. We retrospectively collected 550 consecutive cases of GC in Fudan University Shanghai Cancer Center from 2010 to 2012. PD‐L1, MMR protein, and HER2 status were detected by immunohistochemistry (IHC). Fluorescence in situ hybridization was further used in HER2 IHC 2+ cases. Cases with at least 1% membranous and/or cytoplasmic PD‐L1 staining in either tumor cells (TCs) or tumor‐infiltrating immune cells (TIICs) were considered as PD‐L1 positive. The correlation between clinicopathological parameters, HER2, MMR, and PD‐L1 expression status was determined using chi‐squared tests. About 37.3% cases (205/550) showed PD‐L1 expression in TCs and/or TIICs. 17.3% cases (95/550) showed PD‐L1 expression in TCs, 34.5% (190/550) cases showed PD‐L1 expression in TIICs. There were 45 deficient MMR (dMMR) cases (8.2%), which showed higher rates of PD‐L1 expression compared with MMR‐proficient carcinomas (60.0% vs. 35.2%, P  = 0.001). HER2 was positive in 66 (12.0%) cases. The expression of PD‐L1 occurred more frequently in HER2‐negative group than HER2‐positive cohorts (39.0% vs. 24.2%, P  = 0.020). The survival analysis revealed that PD‐L1 was not associated with prognosis. This study evaluated the association between the PD‐L1 expression and a specific subgroup (dMMR and HER2‐negative) in a large Asian cohort of GC. GC patients with dMMR and HER2‐negative status exhibited higher PD‐L1 expression rates. Our finding indicated that MMR and HER‐2 status might be potential biomarkers for anti‐PD‐L1 therapy. Abstract : PD‐L1 expression in GC is correlated significantly with dMMR and HER2‐negative status. And PD‐L1 expression was not related to GC patients' prognosis. PD‐1/PD‐L1 checkpoint inhibitors might become a novel therapy strategy to HER2‐negative patients.